Mao-Nixon Meeting 1972: National Interest at the Core - Lawoju, Niraj (Khwopa Journal, 2025)
Meeting between Chinese leader Mao Zedong and US President Richard Nixon on February 21, 1972 was an imperative turning point in the contemporary world history. It played a decisive role to end the cold war and begin a new phase of world politics. ‘The New Normal’ developed after the historic meeting has been influencing contemporary world politics in many ways. Thus, even after more than half a century, significance and consequences of the meeting is widely discussed and highlighted often. This paper basically studies on the significance and consequences of the meeting from classical realist perspective. Both the US and China represent different political systems and had a long past of mutual negation and refutation. They even fought the Korean War. Against this backdrop, what made the two world leaders with totally different political ideologies and philosophies come together? How the realist school of thought and the national interests was prevalent behind this landmark meeting? With assistance of historical texts, reminisces, relevant books, academic papers, analysis and newspaper commentaries, this paper studies the role the classical realist school played to push both states to come together and normalize bilateral relation. It is a qualitative analytical study based on published secondary data and analysis. This study contributes to understand the background of evolution of the present world order and helps to analysis the current world politics.